Letter - Soler, Jovian
025a-0003-001 UNION GENERAL DE TRABAJADORES DE ESPANA. Delegation in Great Britain. Paddington Trades Council 494 Harrow Road, London, W.9. Sir Walter Citrine General Secretary of the T.U.C. Dear Sir: There axists among the Spanish refugees in Great Britain a percentage affiliated to the General Workers' Union of Spain (U.G.T.) 63 of whom having considered the necessity of unity met together on September 27th last to elect a managing committee of three members and to establish contact with our National Executive Committee in Mexico. The task wich this Delegation proposes to carry out under the present circumstances is summarized by the following points: a) To group the affiliated members of our national organization resident in Great Britain around our National Executive Committee with a view to the future in Spain, to inform them of the activities of our organization and mantain their attention towards the Spanish problems. b) To induce them to enter the British Trades Union corresponding to their respective activities. c) To increase their enthusiasm for the war and for their work, with the object of raising to the maximum their output and production for the benefit of the democratic front for liberty. Immediately after the meeting we informed our National Executive Committee of our agreement but doubtless owing to the difficulties of communication we have just received their cable, approving the formation of our Delegation and reading as follows: "JOVIAN SOLER 22 INVERNESS TCE LONDON W 2 EXECUTIVE COMMITTEE SENDS IN NAME UGT SPAIN SALUTE TRADES UNIONS TO THEM CONFIRM FRATERNAL. DELEGATION COMPOSED LUIS ESPINAR JOVIAN SOLER FRANCISCO ALBERT RAMON GONZALEZ PEÑSA PRESIDENT AMARO ROSAL SECRETARY". Therefore now that we are officially constituted, we add to the greetings of our Executive Committee our own greetings and our most fervent desire to tighten de bonds of union between ourselves and our British companions in their heroic struggle against the fascist hordes, who are perpetrating against the peoples of the world the same crime wich they committed against the Spanish people. With our most ardent desire for the triumph of the Allied cause, For the Delegation of the U.G.T. of Spain in Great Britain, [Jovian Soler] Secretary 292/946/25a/3